Cardiovascular disease and non-communicable disease behavioral risk factor screening in Rostov-na-Donu citizens - S. E. Glova; L. I. Katelnitskaya; L. A. Khaisheva; S. A. Pleskachev; A. N. Elizarov; V. N. Brazhensky; S. V. Konovalchuk; Z. A. Kodzoeva; M. S. Litovkina; O. I. Oboenko; M. E. Khasanova; E. V. Khorolets (Российский кардиологический журнал)
A cardiovascular disease (CVD) screening study of 1350 Rostov-na-Donu citizens was performed. According to calculated clinical sensitivity and specificity, perspectives of «Cardiovisor - Obs « device use, as primary indicator of heart health and regulatory mechanisms status in screening studies, were determined. Among Rostov-na-Donu citizens, leading behavioral risk factors for non-communicable disease included smoking, low physical activity, and unhealthy diet, resulting in overweight and obesity. There is a need for special preventive program focused on suboptimal ecology region inhabitants.